Konfrontasi : Malaysia, Britain, Indonesia dan isu Melayu Raya, 1963-1966 - Nik Anuar Nik Mahmud (1998)
History of the Malaysia-Indonesia conflict
Bibliografi : p. 247 - 250
Keywords: Malaysia -- Foreign relations -- Indonesia; Malaysia -- History; Indonesia -- History